Mg and Ti codoping effect on the piezoelectric response of aluminum nitride thin films - Anggraini, Sri Ayu; Uehara, Masato; Yamada, Hiroshi; Akiyama, Morito (Scripta materialia, 2019)
Enhancement of the piezoelectric response (d33) of aluminum nitride (AlN) was attempted by incorporating Mg and/or Ti into AlN. Addition of either Mg or Ti as a single dopant was unable to effectively increase the d33 of AlN. However, the d33 could be augmented when both Mg and Ti were codoped into AlN. The optimum d33 (9.1 pC/N) was observed when Mg to Ti ratio was 1.3 and the (Mg + Ti) concentration was approximately 18 at.%. In this study, effect of Mg and Ti co-dopants on the d33 of thin films was elucidated from changes in crystallinity and chemical surface state. [Display omitted]